Specifics of management of alternative schools in the Czech Republic and beyond - Soukup, Vladimír; Lukeš, Martin, 1976-; Mareš, Jan, 1986-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
The goal of this thesis is to understand if there are differences in managing an alternative school as opposed to a traditional one, and if so, how it is different. Furthermore, the thesis aims to provide possible solutions to some of the challenges alternative schools are typically facing. The research is based on data from close to twenty open-structure interviews with alternative schools mostly from the Czech Republic, but also from the USA, and the UK. In particular, we focused on two alternative education movements; democratic schools and Waldorf schools. We have found out that, indeed, there are differences between management in alternative and traditional schools. Among the most noticeable differences in managing alternative schools are: Democratic and authoritative managerial styles are used much more than coercive style; they have a clear purpose and, to various extend, a defined vision of what they try to achieve; they have little standardised processes and structures. We have further discovered that some of the most common challenges for alternative schools are: financial difficulties, scaling up their impact, balance between democracy and efficiency, setting the right culture, managing student progress beyond the school to other academic institutions. This thesis gives alternative school managers a unique insight into the best-case practices of other alternative schools, and ideas they can implement to push their school further. The thesis also confirms that management of alternative schools is, indeed, very different from traditional ones, and these differences need to be taken into consideration in further studies of this subject.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses